2021
DOI: 10.3390/ijerph182312501
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dysfunctional Movements and Asymmetries in Children and Adolescents Using the Functional Movement Screen—A Narrative Review

Abstract: The Functional Movement Screen (FMS) is a screening tool that identifies dysfunctional movements in seven test items requiring an interplay of cognitive, perceptual, proprioceptive, and motor functions that involve muscular strength/endurance, flexibility, mobility, coordination, and balance. The results of the FMS include an overall composite score, scores on the individual test items, and identification of compensatory movement patterns and left-right asymmetries on 5 bilateral test items. Although there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 107 publications
(424 reference statements)
0
7
0
Order By: Relevance
“…Considering the importance of reporting the prevalence of asymmetrical and dysfunctional scores among adolescents [ 41 ], we analyzed the ratio of asymmetric and individual item scores of 1 point or less. The result showed that two groups had high asymmetric prevalence in the five separate items.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of reporting the prevalence of asymmetrical and dysfunctional scores among adolescents [ 41 ], we analyzed the ratio of asymmetric and individual item scores of 1 point or less. The result showed that two groups had high asymmetric prevalence in the five separate items.…”
Section: Resultsmentioning
confidence: 99%
“…Girls performed better on the deep squat and the active straight leg raise. In a group of elite junior athletes 16 to 20 years of age, there were no sex differences in any of the individual functional screen test items [13]. There were several possible explanations for sex differences in performance observed in some studies, such as physiological and biomechanical (muscle performance and movement control patterns), anatomical (differences in joint architecture and mobility), and sociocultural (differences in participation in activity and sport) factors.…”
Section: Introductionmentioning
confidence: 89%
“…Both Intrinsic and extrinsic factors could explain the differences in performance between males and females. Intrinsic factors include but are not limited to skeletal activation, neuromuscular control levels, motor control strategy, and tness level [6, 13,21]. External factors such as maturation and tness level are also relative to performance differences in sex [20].…”
Section: Dynamic Strengthmentioning
confidence: 99%
See 2 more Smart Citations